Pengembangan Bahan Ajar Materi Trigonometri Berbantuan Software iMindMap pada Siswa SMA - Putra, Rizki Wahyu Yunian; Anggraini, Rully (Al-Jabar: Jurnal Pendidikan Matematika, 2016)
The purpose of this study is to find out how to develop teaching material trigonometric material aided iMindMap software. This type of research is research and development (R and D). Sampling was done at SMAN 2 Negeri Katon Pesawaran. The results of the assessment are: the expert assessment of the material giving a score of 85,000 percent is categorized as highly feasible, the design expert scores 87,500 percent rating are categorized as highly feasible, and the media expert gives the scoring score of 79.167 percent categorized as feasible In small group trials, an average of 3.612 was obtained with very decent category. Then a large group trial obtained an average of 3,631 with very decent category. It can be concluded that the iMindMap software-triggered Trigonometry software module is categorized as very feasible and interesting to use in high school equivalent learning on Trigonometry material.